Պաղաղբյուրի ժայռապատկերների խումբը - Մ. Վ. Հերլես; Ռ. Հ. Դավթյան (ՀՀ ԳԱԱ հրատ.)
Пещера с рассматриваемыми петроглифами находится к западу от деревни Пагагбюр (Марз Лори, РА), на северном берегу речки Сарнагбюр. Скала покрыта слоем из железа и марганца, на котором сохранились изображения. The rock shelter where the petroglyphs under consideration were found lies to the west from the village Paghaghbyur (Lori Region, RA), in the northern side of the tiny river Sarnaghbyur.
Keywords: Auxiliary Sciences of History; CC Archaeology